The spread of multi drug resistant infections is leading to an increase in the empirical antibiotic treatment failure in cirrhosis: a prospective survey. - Manuela Merli; Cristina Lucidi; Vincenza Di Gregorio; Marco Falcone; Valerio Giannelli; Barbara Lattanzi; Michela Giusto; Giancarlo Ceccarelli; Alessio Farcomeni; Oliviero Riggio; Mario Venditti (PLoS ONE, 2015)
The spread of multi-resistant infections represents a continuously growing problem in cirrhosis, particularly in patients in contact with the healthcare environment.Our prospective study aimed to analyze epidemiology, prevalence and risk factors of multi-resistant infections, as well as the rate of failure of empirical antibiotic therapy in cirrhotic patients.All consecutive cirrhotic patients hospitalized between 2008 and 2013 with a microbiologically-documented infection (MDI) were enrolled. Infections were classified as Community-Acquired (CA), Hospital-Acquired (HA) and Healthcare-Associated (HCA). Bacteria were classified as Multidrug-Resistant (MDR) if resistant to at least three antimicrobial classes, Extensively-Drug-Resistant (XDR) if only sensitive to one/two classes and Pandrug-Resistant (PDR) if resistant to all classes.One-hundred-twenty-four infections (15% CA, 52% HA, 33% HCA) were observed in 111 patients. Urinary tract infections, pneumonia and spontaneous bacterial peritonitis were the more frequent. Forty-seven percent of infections were caused by Gram-negative bacteria. Fifty-one percent of the isolates were multi-resistant to antibiotic therapy (76% MDR, 21% XDR, 3% PDR): the use of antibiotic prophylaxis (OR = 8.4; 95%CI = 1.03-76; P = 0,05) and current/recent contact with the healthcare-system (OR = 3.7; 95%CI = 1.05-13; P = 0.04) were selected as independent predictors. The failure of the empirical antibiotic therapy was progressively more frequent according to the degree of resistance. The therapy was inappropriate in the majority of HA and HCA infections.Multi-resistant infections are increasing in hospitalized cirrhotic patients. A better knowledge of the epidemiological characteristics is important to improve the efficacy of empirical antibiotic therapy. The use of preventive measures aimed at reducing the spread of multi-resistant bacteria is also essential.